2019
DOI: 10.12783/dtem/icaem2019/31031
|View full text |Cite
|
Sign up to set email alerts
|

Game on: Engaging Tourists through Gamification

Abstract: Gamification has gained up growing attention from researchers of multiple fields including education, health care and marketing. It is believed that gamification of tourism can contribute to a richer experience and higher level of satisfaction. This paper tries to elaborate the design progress of gamification in tourism fields. It identifies the key game design elements to meaningful gamification, and sort out the 6D principle of design framework. An application designed by Disneyland are presented as a case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many studies have shown the positive effect of VE in various types of training, such as healthcare [34], tourism [35], and education [36,37]. Maiano et al [38] proposed a virtual situation composed of potentially harmful content that can cause real stress.…”
Section: Virtual Environmentsmentioning
confidence: 99%
“…Many studies have shown the positive effect of VE in various types of training, such as healthcare [34], tourism [35], and education [36,37]. Maiano et al [38] proposed a virtual situation composed of potentially harmful content that can cause real stress.…”
Section: Virtual Environmentsmentioning
confidence: 99%